Path analysis of exogenous variables against technology adoption levels of dairy cattle in West Sumatera - Tati Herawati; Dwi Priyanto (Indonesian Center for Animal Research and Development (ICARD), 2017)
Path analysis of the regression equation can be used to see the direct and also indirect influence of some exogenous variables against endogenous variables. The rate of feed technology adoption as an endogenous variables can be directly or indirectly influenced by some exogenous variables. The purpose of this research was to test multiple exogenous characteristics variables of dairy cows farms against the feed technology adoption rate as endogenous variables, through path analysis. Research conducted in the city of Padang Panjang, West Sumatra in particular farmer group of dairy cattle in 2016. Endogenous variable is the level of adoption of feed technology (Z). Whereas the exogenous variables are the level of education (X1), the age of farmer (X3), the amount of cow's lactation (X2), farm scale (Y1) and milk production (Y2). The last two variables are variables which are bridging the influence indirectly. Obtained results showed that only X3 which directly influenced Z, with a value of ρZx3 = 0.834 and P = 0.018. Other variables X1 and X2 partly significantly influenced Y1 and X2 significantly influenced Y2 with value of path coefficient in successively ρy1x1 = 0.133 and P = 0.040; ρy1x2 = 0.982 and P = 0.000; ρy2x2 = 0.841 and P = 0.008. Therefore, there was no special model of causal relationships between the empirical variables X and Y against Z, except the X3 which had structure model Z = ρZx3 X3 + ρZε2 = 0.834 X3 + 0.217 ε2. It was concluded that the age strongly influenced the feeding technology adoption. The older the age of farmers, the more difficult for adopting recommended technology.